Global vegetation zonation and terrestrial climate of the warm Early Eocene - Nick Thompson; Ulrich Salzmann; David K. Hutchinson; Stephanie L. Strother; Matthew J. Pound; Torsten Utescher; Julia Brugger; Thomas Hickler; Emma P. Hocking; Daniel J. Lunt (Earth-Science Reviews, 2025)

Synchrotron X-ray Fluorescence Microscopy Reveals Trace Elemental Indicators of Life History in Marsupial Teeth - William M. G. Parker; Justin W. Adams; David P. Hocking; Erich M. G. Fitzgerald; Geoff Shaw; Marilyn B. Renfree; Alistair R. Evans (Biological Trace Element Research, 2025)
As teeth develop, their mineralised composition is a bio-recorder of diet, environment, and growth. High-resolution elemental mapping provides a tool to reveal records of life history within teeth. The relative concentrations of a range of trace elements change between in utero development, birth, and weaning in eutherian mammals. Marsupials, however, have a different mode of development: altricial birth and growth within the pouch facilitated by compositional transitions in milk. How these differences alter patterns of elemental mineralisation and become recorded in marsupial teeth is previously unknown. This study analyses the distribution of calcium (major element), zinc (actively incorporated trace element), and strontium (passively incorporated trace element) in the teeth of five species of diprotodontian marsupial using synchrotron X-ray fluorescence microscopy. We find that the diprotodontian lower incisor concatenates elemental variation from across the molariform dentition, preserving a prolonged record of life history in four of the five species. Patterns of elemental incorporation in enamel, dentine, and cementum are presented, with Ca, Zn, and Sr having differing distributions. Zn accretion indicates a role in mineralisation and/or prevention of tooth degradation. Zn also demarcates incremental cementum lines. Sr is shown to be passively incorporated into marsupial teeth, with increasing Sr concentration in milk recorded in dental tissues formed contemporaneously. Older individuals have oscillatory signals in Sr that appear linked to seasonality. These findings highlight some similarities between eutherian and marsupial trace element incorporation, particularly in the distribution of Zn. Sr signals in marsupial teeth record key aspects of life history.

Traditional and digital examination of the baculum of a leopard seal ( Hydrurga leptonyx ) - James P. Rule; Hazel L. Richards; Tahlia I. Pollock; David P. Hocking; Alistair R. Evans (Marine Mammal Science, 2024)

Suction causes novel tooth wear in marine mammals, with implications for feeding evolution in baleen whales - Felix G. Marx; David P. Hocking; Travis Park; Tahlia I. Pollock; William M. G. Parker; James P. Rule; Erich M. G. Fitzgerald; Alistair R. Evans (Journal of Mammalian Evolution, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Dynamics and predicted distribution of an irrupting ‘sleeper’ population: fallow deer in Tasmania - Calum X. Cunningham; George L. W. Perry; David M. J. S. Bowman; David M. Forsyth; Michael M. Driessen; Matt Appleby; Barry W. Brook; Greg Hocking; Jessie C. Buettel; Ben J. French; Rowena Hamer; Sally L. Bryant; et al. (Biological Invasions, 2022)

Percussive underwater signaling in wild gray seals - David P. Hocking; Ben Burville; William M. G. Parker; Alistair R. Evans; Travis Park; Felix G. Marx (Marine Mammal Science, 2020)

A rare observation of group prey processing in wild leopard seals (Hydrurga leptonyx) - James R. Robbins; Dion Poncet; Alistair R. Evans; David P. Hocking (Polar Biology, 2019)

Chew, shake, and tear: Prey processing in Australian sea lions ( Neophoca cinerea ) - David P. Hocking; Monique A. Ladds; David J. Slip; Erich M. G. Fitzgerald; Alistair R. Evans (Marine Mammal Science, 2017)
Pinnipeds generally target relatively small prey that can be swallowed whole, yet often include larger prey in their diet. To eat large prey, they must first process it into pieces small enough to swallow. In this study we explored the range of prey‐processing behaviors used by Australian sea lions ( Neophoca cinerea ) when presented with large prey during captive feeding trials. The most common methods were chewing using the teeth, shaking prey at the surface, and tearing prey held between the teeth and forelimbs. Although pinnipeds do not masticate their food, we found that sea lions used chewing to create weak points in large prey to aid further processing and to prepare secured pieces of prey for swallowing. Shake feeding matches the processing behaviors observed in fur seals, but use of forelimbs for “hold and tear” feeding has not been previously reported for other otariids. When performing this processing method, prey was torn by being stretched between the teeth and forelimbs, where it was secured by being squeezed between the palms of their flippers. These results show that Australian sea lions use a broad repertoire of behaviors for prey processing, which matches the wide range of prey species in their diet.

Prey capture and processing behaviors vary with prey size and shape in Australian and subantarctic fur seals - David P. Hocking; Erich M. G. Fitzgerald; Marcia Salverson; Alistair R. Evans (Marine Mammal Science, 2016)
When hunting at sea, pinnipeds should adapt their foraging behaviors to suit the prey they are targeting. We performed captive feeding trials with two species of otariid seal, Australian fur seals ( Arctocephalus pusillus doriferus ) and subantarctic fur seals ( Arctocephalus tropicalis ). This allowed us to record detailed observations of how their foraging behaviors vary when presented with prey items that cover the full range of body shapes and sizes encountered in the wild. Small prey were captured using suction alone, while larger prey items were caught in the teeth using raptorial biting. Small fish and long skinny prey items could then be swallowed whole or processed by shaking, while all prey items with body depths greater than 7.5 cm were processed by shaking at the water's surface. This matched opportunistic observations of feeding in wild Australian fur seals. Use of “shake feeding” as the main prey processing tactic also matches predictions that this method would be one of the only tactics available to aquatic tetrapods that are unable to secure prey using their forelimbs.

Leopard seals (Hydrurga leptonyx) use suction and filter feeding when hunting small prey underwater - David P. Hocking; Alistair R. Evans; Erich M. G. Fitzgerald (Polar Biology, 2013)